Quantitative Analysis Of Bacterial Contamination In Dental Laboratory Air - Diana Diaconu; Monica Tatarciuc; Diana Tatarciuc; Anca Vițalariu (Romanian Society of Oral Rehabilitation, 2013)
Diana Diaconu, Monica Tatarciuc, Diana Tatarciuc, Anca Vițalariu, The aim of this study was to analyse quantitative air pollution in dental laboratory at different times of the daily activity. We used the method of collection by sedimentation (Koch) which consisted of opening and exposure of Petri dishes with culture medium-based agar. Five samples were placed in different work areas in all three rooms of the dental laboratory. Recordings were made at the beginning of the workday, during the execution of certain specific manoeuvres and at the end of working day. All data were statistically processed, results are expressed as mean values recorded for each point of determination. Results emphasize the importance of staff awareness of dental labs on health risks caused by air contamination workspaces.